2023
DOI: 10.1002/ana.26825
|View full text |Cite
|
Sign up to set email alerts
|

Higher Glycemic Index and Glycemic Load Diet Is Associated with Slower Disease Progression in Amyotrophic Lateral Sclerosis

Ikjae Lee,
Hiroshi Mitsumoto,
Seonjoo Lee
et al.

Abstract: ObjectiveHigh‐caloric diets may slow the progression of amyotrophic lateral sclerosis; however, key macronutrients have not been identified. We examined whether dietary macronutrients are associated with the rate of progression and length of survival among the prospective cohort study participants.MethodsParticipants with a confirmed diagnosis of sporadic amyotrophic lateral sclerosis enrolled in the Multicenter Cohort Study of Oxidative Stress were included (n=304). We evaluated baseline macronutrient intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…Similar differences in dietary intake based on DGI and DGL levels have also been documented in earlier research with different study populations ( Lee et al, 2023 ; Sluijs et al, 2013 ; Zhao et al, 2022 ). For instance, an earlier study found that dietary protein, saturated fat, monounsaturated and polyunsaturated fatty acids, fiber intakes were higher in the first quartile DGI and DGL than the others ( Zhao et al, 2022 ).…”
Section: Discussionsupporting
confidence: 83%
“…Similar differences in dietary intake based on DGI and DGL levels have also been documented in earlier research with different study populations ( Lee et al, 2023 ; Sluijs et al, 2013 ; Zhao et al, 2022 ). For instance, an earlier study found that dietary protein, saturated fat, monounsaturated and polyunsaturated fatty acids, fiber intakes were higher in the first quartile DGI and DGL than the others ( Zhao et al, 2022 ).…”
Section: Discussionsupporting
confidence: 83%